Knowledge and Practice of Self-medication among Undergraduate Medical Students - Karmacharya, Anishma; Uprety, Bipashwi Nath; Pathiyil, Ravi Shankar; Gyawali, Sudesh (Journal of Lumbini Medical College, 2018)
Introduction: Self-medication is an important aspect of self-care. It is a common practice in society and medical students are no exception. The aim of this study was to explore the knowledge and practice of self-medication among students of a medical school in Western Nepal.Methods: A cross sectional study was conducted among basic science and clinical students after obtaining prior consent from those willing to participate. Respondents’ degree of agreement with a set of 25 statements was noted using Likert scale to assess their knowledge. The practice of self-medication was studied by asking about the use of selected groups of medicines during the past one-year period and noting the pattern of use.Results: Three hundred and thirty of the 356 students (92.6%) participated in the study. Mean knowledge score was 93.2 (SD = 8.1). Self-medication was practiced by 83.3% (n = 275) of respondents. Knowledge about self-medication differed among respondents according to gender (p = 0.03) and nationality (p = 0.04) but not other variables. Practice of self-medication was associated with father’s profession (p = 0.03) and nationality of the respondents (p = 0.04).Conclusions: Students’ knowledge about self-medication was good and they commonly practiced self-medication. Pain-killers were the most commonly used drug. DOI: https://doi.org/10.22502/jlmc.v6i1.174